METAL ARCHES «DAMON SYSTEM» AND THEIR POTENTIAL APPLICATION IN ORTHODONTICS CLINIC - D. S. Dmitrienko; V. V. Shkarin; V. O. Torokhova; A. V. Mnatsakanyan; V. V. Timircheva (Современная наука и инновации)
The measurements of the diagonal and latitudinal parameters of dental arches in people with physiological occlusion at various gnatic and odontometric variants of dental arches, as well as the results of the biometric research of plaster models of the jaws are presented. It was revealed that the metal arches «DAMON SYSTEM» can be used after the individual preformation depending on the gnatic and dental type of arches and features of diagonal and transversal dimensions.